Spatial Equity Analysis of Public Facilities in South Tangerang City - Bimantara Faqih; Akmal Ramadhan; Attalitha Nabilah Daniswara; Shelsi Cindy Avira; Syaima Salsabil Safinatunnajah (Jurnal Teknik Sipil dan Lingkungan, 2026)
The rapid urban expansion of the Greater Jakarta metropolitan area has placed significant pressure on public service provision in its satellite cities, including South Tangerang City. Despite recording the highest Human Development Index (HDI = 84.16) among the Bodetabek region, access to public facilities remains unequal across sub- districts. This study aims to analyse the spatial equity of public facility distribution in South Tangerang City across three sectors: education (primary, junior, and senior high schools), health (public health centres and hospitals), and public transportation (bus stops and train/commuter rail stations). Spatial analysis was performed using two complementary methods: Nearest Neighbour Analysis (NNA), which computes the Nearest Neighbour Index (NNI) — a dimensionless ratio comparing observed mean inter-facility distances to those expected under a random spatial distribution — to identify whether facility point patterns are clustered (NNI < 0.7), random (0.8–1.4), or dispersed (NNI > 1.5); and network-based Service Area Analysis, which delineates reachable zones from each facility via the actual road network. Data were sourced from OpenStreetMap (OSM) and the Indonesian National Topographic Map (RBI BIG 2022), processed in QGIS using the QuickOSM plugin and QNEAT3 network analysis toolbox. Results indicate that most facilities exhibit a clustered distribution pattern, particularly bus stops (NNI = 0.298), schools (NNI = 0.603), and hospitals (NNI = 0.603). Service area analysis revealed significant blank spots primarily in health and transportation sectors: four sub-districts — Pakulonan, Pondok Cabe Udik, Keranggan, and Pakujaya — fall outside the ideal community health centers/clinics service radius, while seven sub-districts are located more than 5 km from the nearest train/commuter rail station. Education and hospital coverage generally meets service standards at the sub-district scale. These findings confirm that public facility distribution in South Tangerang City has not fully satisfied the principle of spatial equity, and that access to public services continues to be determined largely by place of residence.